Isolation of Cellulolytic Microbes from Bio-Slurry - Muammar, Arief; Manullang, Maria; Arjuna, Mesha; Retnaningrum, Endah (Faculty of Mathematics and Natural Sciences (FMIPA), Universitas Negeri Padang, Indonesia, 2021)
Cellulolytic microbes produce cellulase enzymes that can degrade cellulose. Cellulolytic microbes are found in many habitats, including in cattle waste (bio-slurry), which is result of hydrolysis of cattle feed ingredients sourced from cellulose. Cellulase enzymes play a role in the process of hydrolyzing cellulose into glucose. This study aims to isolate cellulolytic microbes from bio-slurry and measure activity of cellulase enzymes in cellulolytic microbes isolated from bio-slurry. We are taking bio-slurry samples with 5 sample points and isolating the microbes in Carboxyl Methyl Cellulose (CMC) medium, cellulase enzyme activity qualitative test with Congo Red Assay, and perform quantitative test with the DNS Assay. Microbial isolates which shows positive results for cellulolytic activity in the qualitative test called SIIC1, SIIIC5, SIIC3. In the quantitative test can be seen based on Optical Density (OD) for cell lysate, SIIC1 0.298; SIIC3 0.186; SIIIC5 0.247; and a 0.332 for blank solution. Whereas supernatant obtain SIIC1 value of 0.237; SIIC3 0.212; SIIIC5 0.198; and 0.195 for blank solution. Based on the results, it can be concluded that the cellulolytic activity of microbes in bio-slurry based on OD values shows good results in supernatant, but it’s not significant enough in the cell lysate.